Melon fruit yield and quality as a function of doses and times of biostimulant application (Research, Society and Development, 2020)
The objective of this study was to evaluate the productivity and quality of melon fruits as a function of the dose and time of application of biostimulant in the conditions of the semi-arid region of Paraíba. The experiment was carried out at the Federal University of Campina Grande, campus of Pombal - PB, Brazil, in a randomized block design in a 4 x 5 split plot scheme, with doses of biostimulant (0; 0.5; 1.0; 1, 5 and 2.0 L ha-1) and in the subset of the biostimulant application times (15; 20; 25 and 30 days before harvest - DAC), in four replications. Characteristics related to fruit production and quality were evaluated. There was no interaction between the factors of dose and application time of the biostimulant in any of the evaluated characteristics. Thus, the highest estimated values of number of fruits per plant, fruit mass and total melon production were obtained with the application of doses ranging from 0.9 to 1.5 L ha-1 and at the time of application it varied from 22,5 to 23.6 DAC. The content of soluble solids increased 5.5% when the biostimulant dose of 2.0 L ha-1 was used and 4.4% when the product was applied 15 days before harvest.